Anticancer activity of glycoalkaloids from Solanum plants: A review - Winkiel, Magdalena Joanna; Chowański, Szymon; Słocińska, Małgorzata (Frontiers in Pharmacology, 2022)
Cancer is still one of the main causes of death worldwide. For this reason, new compounds that have chemotherapeutic potential have been identified. One such group of substances is Solanaceae glycoalkaloids (GAs). They are natural compounds produced by plants widely used in traditional medicine for healing many disorders. Among others, GAs exhibit significant antitumor properties, for example, a strong inhibitory effect on cancer cell growth. This activity can result in the induction of tumor cell apoptosis, which can occur via different molecular pathways. The molecular mechanisms of the action of GAs are the subject of intensive research, as improved understanding could lead to the development of new cancer therapies. The genetic basis for the formation of neoplasms are mutations in protooncogenes, suppressors, and apoptosis-controlling and repair genes; therefore, substances with antineoplastic properties may affect the levels of their expression or the levels of their expression products. Therapeutic compounds can be applied separately or in combination with other drugs to increase the efficiency of cancer therapy; they can act on the cell through various mechanisms at different stages of carcinogenesis, inducing the process of apoptosis, blocking cell proliferation and migration, and inhibiting angiogenesis. This review summarizes the newest studies on the anticancer properties of solanine (SN), chaconine (CH), solasonine (SS), solamargine (SM), tomatine (TT) and their extracts from Solanum plants.